Pengaruh Fasilitas, Harga, dan Promosi Penjualan Terhadap Loyalitas Wisatawan Obyek Mata Air Cokro Klaten - Satria, Hera Budi; , Lukman Hakim, SE, MSi (2016)
Abstract This study aims to determine the effect of amenities, price, and promotion of sales to visitor loyalty Object Spring Cokro in Klaten. The population of this research is all the visitors who are visiting in the Object Spring Cokro Klaten. The samples in this study conducted by random sampling. The study sample was obtained by 100 respondents. Mechanical Analysis of the data in this study using validity, reliability test, classic assumption test, multiple regression analysis, t test, F test, and the test of determination. The results of this study show: facilities and significant positive effect on visitor loyalty. Based on the regression coefficients of the variables of the facility amounted to 0,244 and the value, thitung> t table (3,245> 1,988) and the significance value <0.05, namely 0.002; price positive and significant impact on visitor loyalty. Based on the regression coefficient of the price variable is equal to 0.456 and tcount> t table (5.957> 1.988) as well as the significance value <0.05 is 0,000; sales promotion and no significant positive effect on visitor loyalty. Based on the regression coefficient of variable sales promotion is 0.022 and tcount> t table (0.290 <1.988) and a significant value> 0.05 is 0.772. Facilities, prices, and sales promotion jointly affect the visitor loyalty, evidenced by F. Test on the F test obtained F count> F table, namely (36.126> 2.70) and the significance value <0.05, namely 0.000 (H0 , H1 accepted); the results of testing the coefficient of determination (R2) shows that the facilities, prices, and sales promotion are able to explain the variability of 53%, while 47% are influenced by other variables not examined. Keywords: Loyalty, Facilities, Pricing, Sales Promotion